2007
DOI: 10.1002/ptr.2229
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activities of the essential oil from Abies koreana

Abstract: The essential oils from an alpine needle leaf of Abies koreana, which is a species native to Korea, was obtained by hydrodistillation with 0.9% (v/w) yield and analysed by GC and GC-MS. Sixty-eight constituents, accounting for more than 95.9% of the total oil composition, were identified. The main compounds with concentrations higher than 3% were borneol (27.9%), alpha-pinene (23.2%), beta-pinene (5.8%), terpinene-4-ol (3.8%), bornyl acetate (3.4%) and alpha-terpineol (3.1%). The antibacterial activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 16 publications
2
31
0
2
Order By: Relevance
“…Studies have shown that pine needle oil has anti-inflammatory and antiblastic effects and can significantly inhibit . biosynthesis (Pichette et al, 2006;Jeong et al, 2007). In another study, a pine needle extract solution was found to inhibit the rate of growth of a mouse transplantable tumor by more than 40% (Loizzo et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Studies have shown that pine needle oil has anti-inflammatory and antiblastic effects and can significantly inhibit . biosynthesis (Pichette et al, 2006;Jeong et al, 2007). In another study, a pine needle extract solution was found to inhibit the rate of growth of a mouse transplantable tumor by more than 40% (Loizzo et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Although, several researchers have reported the efficiency of plant extracts to suppress 28°C (day) and 22°C (night) and 16 h light: 8 h dark photoperiod. The highly infected leaves were gently scraped to collect conidia and washed with sterile distillated water (SDW), then the spores were suspended in tubes and filtrated through sterilized cheese cloth ( Jeong et al, 2007). The spore suspensions were determined by a hemocytometer and adjusted to concentration 1 × 10 5 conidia ml -1 for inoculating plants.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous reports, the yields of essential oils from the needles, twigs and cones, as well as twigs with needles of A. koreana (by after 5 h of hydrodistillation) were 1.0%, 0.64%, 0.42% and 0.83%, respectively [9]. In other studies, 0.6%, 0.53%, and 0.9% of essential oil yields were obtained from the needles of A. koreana by Lee and Hong [2], Oh et al [3] and Jeong et al [10] respectively. In the present study, it was observed that the harvesting times highly influenced on the essential oil yield with the highest value in August (1.20%) and the lowest value in April (0.76%).…”
Section: Resultsmentioning
confidence: 89%
“…In addition, the supercritical carbon dioxide extract from the needles of A. koreana exhibited memory enhancing effect in mice [8]. Previously, some authors reported the essential oil composition and its antimicrobial activity of A. koreana of different origins [2,3,9,10]. However, the published data about the essential oil composition of A. koreana has been extensively varied between the authors.…”
Section: Introductionmentioning
confidence: 99%